UNDERSTANDING THE PRECURSORS OF 3R (REDUCE, REUSE, RECYCLE) BEHAVIOR TOWARD E-COMMERCE PACKAGING WASTE IN INDONESIA - Raihana, Jasmine
E-commerce has changed the way consumers shop for their necessities. Not only it provides a wide range of product options, it also offers a more practical shopping experience for the consumers. The development of e-commerce is also accelerated by the COVID-19 pandemic, where the consumers were unable to go to physical store themselves. Despite the pandemic has come to an end, e-commerce has now become an integral part in consumers’ shopping behaviour as they were still going to use the platforms to fulfil their needs. However, the rise of e-commerce has caused an issue on its own. Online shopping generates more waste than its offline counterpart. The waste came from the packaging materials used by the sellers to protect their goods, such as bubble wraps, plastics, papers, and cardboard. Most of these wastes were still discarded to the landfills. With the excessive materials and the consumers’ high shopping intensity, the e-commerce activities might give a great contribution on the piling up waste on the nature. If not being treated properly, the e-commerce waste might lead to a serious environmental problem. The novelty of this research lies in the exploration of e-commerce waste management activities on the consumers’ level. Despite the pre-existing research on wase management, such as recycling and waste separation, the current phenomenon and the uniqueness of e-commerce packaging materials needed to be examined on its own. Consumers’ contribution in this issue is deemed vital as they are the one who needs to deal with the excessive packaging materials waste once they receive the package. We highlighted the 3R (reduce, reuse, recycle) concept as a pro-environmental waste management activities consumers can do toward their e-commerce waste. As a part of pro environmental activities, we assume that the 3R behaviour heavily relied on the moral obligation consumers feel. Thus, following the Norm Activation Model (NAM) theory, this study aimed to uncover the antecedents of consumers’ 3R behaviour toward their e-commerce waste. We examined four aspects as the precursors of personal norm: awareness of consequences, ascription of responsibility, information, and social norms. Furthermore, personal norms, social norms, convenience, and perceived behavioural control were tested as the antecedents of behavioural intention. This research followed exploratory sequential mixed method, where qualitative data collection was first conducted before the quantitative one. We used semi-structured interviews as the qualitative data collection to generate more understanding about the phenomenon being studied in this research. The result of the semi-structured interview also highlighted the urgency of this issue and consumers’ perception toward their own e-commerce waste. We utilised selfadministered questionnaire as the quantitative data collection method, where we obtained 315 data from e-commerce users in Indonesia who had performed at least once for the past six months. While the open-ended questions were analysed using content analysis, we used Partial Least Square (PLS) as the statistical analysis method for the numerical data. The findings from PLS-SEM showed the relationship between each variable tested in this study. Awareness of consequences, ascription of responsibilities, and social norm were proven to have a significant influence toward personal norms. On the other hand, the relationship between information and personal norm were found to be insignificant. Convenience was proven to have a significant relationship with perceived behavioural control. Personal norm, social norm, and perceived behavioural control all had significant relationship with the behavioural intention. The behavioural intention had a significant relationship with the 3R behaviour. It also mediated the relationship between personal norm, social norm, and perceived behavioural control with the 3R behaviour. Additionally, we performed netnography to gain insights from social media about the consumers’ opinion regarding this issue. This research extends the current theoretical knowledge in e-commerce and waste management literature by providing new insight of e-commerce waste management from the consumers’ point of view. The finding of this research also offers managerial implications for all involved stakeholders, including e-commerce providers and policy makers, as the foundation in solving environmental issues related e-commerce activities. Keywords: waste management, e-commerce waste, norm activation model, 3R behaviour concept, consumers behaviour kenyaman, dan control perilaku pun diuji sebagai factor yang mempengaruhi intensi perilaku. Riset ini dilakukan dengan mengikuti metode penelitian campuran, yaitu exploratory sequential. Pada riset ini, pengambilan data secara kualitatif dilakukan terlebih dahulu, kemudian diikuti oleh pengambilan data kuantitatif. Interview semi-terstruktur dilakukan sebagai bentuk pengambilan data kualitatif untuk memberikan konteks dan pemahaman yang lebih dalam mengenai isu ini. Hasil dariinterview semi-terstruktur menitikberatkan pentingnya penelitian ini dan memberikan pemahaman mengenai persepsi konsumen terhadap isu sampah kemasan e-commerce ini. Kami melakukan kuisioner sebagai bentuk pengambilan data kuantitatif, di mana kami mendapatkan data dari 315 orang konsumen yang melakukan transaksi berbelanja minimal satu kali selama enam bulan terakhir. Pertanyaan terbuka pada kuisioner dianalisis secara kualitatif, sementara data numerik dianalisis dengan menggunakan Partial Least Square (SEM-PLS). Hasil penemuan dari SEM-PLS menunjukan signifikansi hubungan masing-masing variable yang diuji pada studi ini. Kesadaran pada konsekuensi, pembentukan tanggung jawab, dan norma sosial dibuktikan memiliki hubungan signifikan dengan norma pribadi. Sementara itu, hubungan informasi dan norma pribadi dinilai tidak signifikan. Kenyamanan dibuktikan memiliki hubungan signifikan dengan control perilaku. Norma pribadi, normal sosial, dan kontrol perilaku memiliki hubungan yang signifikan terhadap intensi perilaku. Selain memiliki hubungan signifikan dengan perilaku 3R, intensi perilaku pun memdiasi hubungan perilaku 3R dengan norma pribadi, norma sosial, dan kontrol perilaku. Sebagai tambahan, kami pun melakukan nentnografi untuk menganalisa pendapat konsumen di media sosial mengenai isu ini. Penelitian ini berkontribusi dalam menambah pengetahuan teoretis mengenai ecommerce dan pengelolaan sampah dengan memberikan masukan baru dari sudut pandang konsumen. Hasil dari penelitian ini pun memberikan implikasi manajerial untuk seluruh pihak terkait, termasuk penyedia e-commerce dan pembuat aturan hukum, sebagai pondasi dalam menyelesaikan masalah lingkungan terkait aktivitas berbelanja online di e-commerce. Kata kunci: pengelolaan sampah, sampah kemasan e-commerce, teori model aktiviasi norma, konsep 3R, perilaku konsumen